Focussed-Ion-Beam Post Processing Technology for Active Devices - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2006)
Focused ion beam (FIB) etching technology is a highly efficient post-processing technique with the functionality to perform sputter etching and deposition of metals or insulators by means of a computer-generated mask. The high resolution and the ability to remove material directly from the sample in-situ make FIB etching the ideal candidate for device prototyping of novel micro-size photonic component design. Furthermore, the fact that arbitrary profile can be etched directly onto a sample without the need to prepare conventional mask and photolithography process makes novel device research with rapid feedback from characterisation to design activities possible. In this paper, we present a concise summary of the research work in Cambridge based on FIB technology. We demonstrate the applicability of focussed ion beam post processing technology to active photonic devices research. Applications include the integration of advanced waveguide architectures onto active photonic components. We documents details on the integration of lens structure on tapered lasers, photonic crystals on active SOA-integrated waveguides and surface profiling of low-cost gain-guided vertical-cavity surface-emitting lasers. Furthermore, we discuss additional functions of FIB in the measurement of buried waveguide structures or the integration of total-internal-reflection (TIR) mirror in optical interconnect structures.